From scroll to sale: how social media triggers and age shape digital consumer decisions through interaction - Abdalla, Reem; Faizal, Shabana; Menon, Nidhi; Mohammed, Arshiya (Frontiers in Communication, 2025)
This study examines how digital stimuli social media trends (SMT), quality of information (QTI), and influencer cues (ICR) shape consumer buying behavior (CBB) through the mediating role of social media interaction (SMI). Drawing on the Stimulus–Organism–Response (S-O-R) model, Uses and Gratifications Theory (UGT), and the Theory of Planned Behavior (TPB), data were collected from 359 Saudi social media users and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings indicate that SMT and QTI significantly enhance SMI, which in turn predicts CBB. However, ICR showed no significant influence, highlighting possible trust erosion or influencer fatigue. Mediation analysis confirmed SMI’s central role between SMT/QTI and CBB, while moderation analysis revealed no significant age-based differences. The adjusted R2 for CBB was 0.276, indicating modest explanatory power. PLS-Predict results showed predictive relevance with limited accuracy. This research repositions social media interaction as a cognitive-emotional mechanism that bridges exposure and behavior. Practically, marketers are encouraged to prioritize credible, engaging content over influencer-centric strategies, particularly in digitally mature markets.